Improvement and Simulation of an Autonomous Time Synchronization Algorithm for a Layered Satellite Constellation. (12th December 2013) - Huang, Feijiang; Lu, Xiaochun; Liu, Guangcan; Sun, Liping; Sheng, Wang; Wang, Yingde
Abstract : Autonomous time synchronization for satellite constellations is a key technology to establish a constellation system time without the use of a ground station. The characteristics of satellite visibility time for layered satellite constellations containing geostationary earth orbit (GEO), inclined geosynchronous orbit (IGSO), and medium earth orbit (MEO) satellites are simulated by establishing a visible satellite model. Based on the satellite visible simulation results for a layered constellation, this study investigates the autonomous time synchronization algorithm that corresponds to the layered constellation structure, analyzes the main error of the time synchronization algorithm, and proposes methods to improve the characteristics of satellite movement in the constellation. This study uses an improved two-way time synchronization algorithm for autonomous time synchronization in the GEO-MEO satellite layer of a layered satellite constellation. The simulation results show that in a condition with simulation errors, the time synchronization precision of this improved algorithm can be controlled within 5 ns and used in high-precision autonomous time synchronization between layered satellite constellations.